LOKPAL AND GOOD GOVERNANCE - Parishkar Shreshth (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
We have not received an adequate benefit from the government for decades since our independence. India is now a young country that is at a transitional stage. Today citizens of India want to utilise all the resources and opportunities most productively. So, good governance is mandatory for total development. Because of the uncertainty about India's country, it is possible only a Lokpal like institution can change peoples' minds about development. We are waiting for a major positive change. Corruption in India is a major concern and is a detriment to the economy. According to research, the bulk of public corruption is financed by a government programme. Now voters in India appreciate the value of their vote. They usually call for the development of a system to reduce corruption. The Lokpal bill against corruption is a good tool, but its implementation has been held back because of a lack of enthusiasm and disappointment. The purpose of this study is to understand voters' thoughts and feelings about the Lokpal bill. This paper highlights the significant issues of Lokpal and its impact on governance.